The DPP-4 inhibitor linagliptin does not prolong the QT interval at therapeutic and supratherapeutic doses - Ring, Arne (Blackwell Science Inc, 2011)
AIM: To evaluate the potential effects of therapeutic and supratherapeutic doses of linagliptin (BI 1356) on the QT/QT(c) interval in healthy subjects. METHODS: The study was a randomized, double-blind, placebo-controlled, four-period crossover study using single oral doses of linagliptin (5 mg and 100 mg), moxifloxacin (400 mg) and placebo. Electrocardiogram (ECG) profiles using triplicates of 12-lead 10-s ECGs were digitally recorded pre-dose and after drug administration. The mean change from baseline (MCfB) of the individually heart rate corrected QT interval (QT(c)I) between 1 and 4 h postdrug administration was the primary end point. Blood samples to measure plasma concentrations of linagliptin and its main metabolite were also obtained. RESULTS: Forty-four Caucasian subjects (26 male) entered the study and 43 subjects completed the study as planned in the protocol. Linagliptin was not associated with an increase in the baseline-adjusted mean QT(c)I, at any time point. The placebo-corrected MCfB of QT(c)I was −1.1 (90% CI −2.7, 0.5) ms and −2.5 (–4.1, –0.9) ms for linagliptin 5 mg and 100 mg, respectively, thus within the non-inferiority margin of 10 ms according to ICH E14. Linagliptin was well tolerated; the assessment of ECGs and other safety parameters gave no clinically relevant findings at either dose tested. Maximum plasma concentrations after administration of 100-mg linagliptin were ∼24-fold higher than those observed previously for chronic treatment with the therapeutic 5-mg dose. Assay sensitivity was confirmed by a placebo-corrected MCfB of QT(c)I with moxifloxacin of 6.9 (90% CI 5.4, 8.5) ms. CONCLUSIONS: Therapeutic and significantly supratherapeutic exposure to linagliptin is not associated with QT interval prolongation.